2008
DOI: 10.1093/pcp/pcn043
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism Selecting the Guide Strand from Small RNA Duplexes is Different Among Argonaute Proteins

Abstract: Double-stranded RNA induces RNA silencing and is cleaved into 21-24 nt small RNA duplexes by Dicer enzyme. A strand of Dicer-generated small RNA duplex (called the guide strand) is then selected by a thermodynamic mechanism to associate with Argonaute (AGO) protein. This AGO-small RNA complex functions to cleave mRNA, repress translation or modify chromatin structure in a sequence-specific manner. Although a model plant, Arabidopsis thaliana, contains 10 AGO genes, their roles and molecular mechanisms remain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
414
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(454 citation statements)
references
References 26 publications
30
414
0
10
Order By: Relevance
“…It is suggested that the difference in size of the identified miRNAs within different families might offer unique functions for the regulation of miRNA biogenesis or gene expression in plants. It is reported that uracil is more represented at the 5′ side of mature miRNAs; the percentage of representation of mature miRNAs having U at the 5′ side of the stem loop is 66.67%, followed by A (14.52%), C (9.68%), and G (9.14%); this is consistent with previous findings (Mi et al, 2008;Montgomery et al, 2008;Takeda et al, 2008;Zhang et al, 2008). It is speculated that the strong bias of uracil in the first 5′ nucleotide position is due to its important role in the recognition of the miRNA by argonaute1 (Zhang et al, 2006b Table 1 and Fig.…”
Section: Resultssupporting
confidence: 91%
“…It is suggested that the difference in size of the identified miRNAs within different families might offer unique functions for the regulation of miRNA biogenesis or gene expression in plants. It is reported that uracil is more represented at the 5′ side of mature miRNAs; the percentage of representation of mature miRNAs having U at the 5′ side of the stem loop is 66.67%, followed by A (14.52%), C (9.68%), and G (9.14%); this is consistent with previous findings (Mi et al, 2008;Montgomery et al, 2008;Takeda et al, 2008;Zhang et al, 2008). It is speculated that the strong bias of uracil in the first 5′ nucleotide position is due to its important role in the recognition of the miRNA by argonaute1 (Zhang et al, 2006b Table 1 and Fig.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to AGO7, AGO2 efficiently incorporated the miR390/miR390* mutant with the flipped central 3-nt ( Supplementary Fig S1 online), suggesting that AGO2 does not inspect the central region for RISC assembly. This is consistent with the previous finding that AGO2 incorporates a wide variety of 5 0 -A small RNAs including viral siRNAs [22][23][24]. miR390/miR390* duplex has two mismatches: a G-U wobble in the seed region (guide position 3) and a G-A mismatch in the central region (guide position 11).…”
Section: Ago7 Inspects the Central Region Of Mir390 Duplexsupporting
confidence: 92%
“…sRNAs with length between 20 and 25 nt were included in our analysis. Previous studies reported that Arabidopsis sRNAs are sorted into distinct AGO complexes depending on the length and 5’ first nucleotide of sRNAs, which has important implications for the functions of miRNAs and siRNAs (Mi et al 2008; Takeda et al 2008). Therefore, we detected the length and 5’ first nucleotide of sRNAs in the two libraries respectively.…”
Section: Resultsmentioning
confidence: 99%